Modulating fibroblast growth factor 21 in hyperphagic OLETF rats with daily exercise and caloric restriction - Fletcher, Justin A. (Appl Physiol Nutr Metab, 2012)
Chronic treatment with fibroblast growth factor 21 (FGF-21) favorably improves obesity and nonalcoholic fatty liver disease (NAFLD) outcomes; however, FGF-21 expression is paradoxically elevated in obese conditions. Here, we sought to determine the effects of obesity prevention by daily exercise (EX) vs. caloric restriction (CR) on hepatic FGF-21 in the hyperphagic, Otsuka Long-Evans Tokushima Fatty (OLETF) rat. Four-week-old male OLETF rats were randomized into groups (n = 7–8 per group) of ad libitum fed, sedentary (OLETF-SED), voluntary wheel running exercise (OLETF-EX), or CR (OLETF-CR; 70% of SED) until 40 weeks of age. Nonhyperphagic, Long-Evans Tokushima Otsuka (LETO-SED) rats served as controls. Both daily EX and CR prevented obesity and NAFLD development observed in the OLETF-SED animals. This was associated with significantly (p < 0.01) lower serum FGF-21 (~80% lower) and hepatic FGF-21 mRNA expression (~65% lower) in the OLETF-EX and OLETF-CR rats compared with the OLETF-SED rats. However, hepatic FGF-21 protein content was reduced to the greatest extent in the OLETF-EX animals (50% of OLETF-SED) and did not differ between the OLETF-SED and OLETF-CR rats. Hepatic FGF-21 signaling mediators — hepatic FGF-21 receptor 2 (FGFR2, mRNA expression), hepatic FGF-21 receptor substrate 2 (FRS2, protein content), and co-receptor β-Klotho (protein content) — were all elevated (60%–100%, ~40%, and +30%–50%, respectively) in the OLETF-EX and OLETF-CR animals compared with the OLETF-SED animals. Daily exercise and caloric restriction modulate hepatic FGF-21 and its primary signaling mediators in the hyperphagic OLETF rat. Enhanced metabolic action of FGF-21 may partially explain the benefits of exercise and caloric restriction on NAFLD outcomes.